Integrated Marketing Communication Solo Art Market Untuk Membangun Brand Awareness - Zon Vanel; Lina Sinatra Wijaya; George Nicholas Huwae; Gracelia Audriana Dewi (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The study aims to find the most effective Integrated Marketing Communication strategy for increasing brand recognition in the Solo Art Market. This study focuses on understanding target audiences' requirements and preferences and the most successful channels and techniques for reaching them. It also investigates the function of storytelling and emotional appeal in developing brand recognition for solo artists. This research is qualitative applied research, which tries to address issues such that the research results may be utilized to benefit individuals or organizations as well as for industrial goals, and it focuses on items whose outcomes can be applied to present and future situations. According to the study's findings, the Solo Art Market's Integrated Marketing Communication approach is a solid platform for raising brand recognition in the community. Due to the absence of instruments employed by Solo Art Market to reach a larger market, Solo Art Market's brand awareness is limited to brand recognition. Brand awareness is the amount of brand awareness that requires help, such as a brand list, image list, or brand stamp. Due to brand recognition, consumers need assistance with the items on sale; yet, Solo Art Market's ingenuity in developing appealing messaging can increase public brand awareness of the market's presence.